Modern Educational Management Practices at Walisongo Islamic Boarding School, Sragen, Central Java to Welcome the Era of Society 5.0 - Ali Muhksin; Toto Suharto; Fauzi Muharrom; Mifedwil Jandra (CV. Media Digital Publikasi Indonesia, 2025)
This article reveals how the process of modern education management is practically implemented in the world of Islamic boarding schools, especially at the Walisongo Islamic Boarding School, Sragen, Central Java. This management is key to the ongoing development and adaption of Islamic boarding school education to the times. The ongoing Society 5.0 era requires Islamic boarding schools to adapt to management methods with new methods, not with old patterns. This requires Islamic boarding school education to be able to adapt in order to produce competent graduates. By using qualitative research methods which focus on field studies, this study examines how the phenomena of Islamic boarding school education must adapt to the framework of society 5.0 which requires a new breakthrough framework in the world of education. They must be able to innovate, be creative and always think forward to produce a good generation. Society 5.0 requires education to be entrenched in a futuristic framework. This means that the patterns that must be developed by educational institutions invite students to be able to adapt to their environment and merge with their society. Not using old patterns that are traditional in nature that are isolated from their society. Therefore, there must be good management in managing an institution as large as an Islamic boarding school. The management carried out must encompass four important aspects, namely planning, organizing, actuating , and evaluating, no longer just focusing on one direction and policy that is not in accordance with the vision and mission of renewal and development of reasoning. This is done by PP Walisongo so that the students can follow the development of the times